ATTITUDES OF PRESCHOOL TEACHER CANDIDATES TOWARDS TEACHING PROFESSION - Şafak ÖZTÜRK AYNAL (Fırat University, 2019)
Occupation is one of the most significant elements of one's life. As in the choice of partners, it is not arbitrary or temporary; on the contrary, it is a concept which covers and characterizes the whole life. In Turkey, with the growing focus on preschool education, the in